AI tools that “wow” your students for better engagement in the classroom - Mokhtar, Rashidah; Jaafar, Nur Huda (Universiti Teknologi MARA, Johor, 2025)
This article explores the transformative potential of Artificial Intelligence (AI) in enhancing student engagement within classroom environments. It provides an overview of AI tools that facilitate interactive learning, streamline assessments, and promote creativity in educational contexts. By categorising AI tools into presentation, content creation, and engagement platforms, the study highlights their role in enhancing instructional delivery, student participation, and assessment practices. The discussion further examines future trends, such as microlearning, personalized learning, and immersive technologies, emphasizing AI’s role in supporting lifelong learning. The article concludes that thoughtful integration of AI enhances teaching efficiency and empowers students to become active participants in their own learning journeys. In the evolving landscape of education, student engagement has become a cornerstone of effective teaching and learning. Traditional lecture-based approaches, while foundational, often fall short in maintaining learners’ attention and motivation. The emergence of AI provides educators with innovative tools that enhance interactivity, personalize learning experiences, and enable efficient content delivery. AI allows educators to design adaptive, data-informed, and dynamic learning environments that align with students’ preferences and capabilities.